Electronic Hasta La Vista (e-HLV): Student Assessment System for Finishing School - CHE ADNAN, AMIRUL AFFIZALHAIRI; HAFIT, HANAYANTI (Applied Information Technology And Computer Science, 2025)
The Electronic Hasta La Vista (e-HLV) Student Assessment System is developed to streamline the assessment process for students, educators, and coordinators in higher education institutions, particularly Universiti Teknologi MARA (UiTM). This system addresses inefficiencies in the current manual processes, such as time-consuming data handling, errors in mark entry, and delays in feedback. The system incorporates features like secure login, automated grading, real-time feedback, and report generation to improve assessment management. The Prototyping methodology is employed, involving iterative development to refine the system based on user feedback. The implementation of the e-HLV System for a web-based platform is done using Visual Studio Code. Based on the results of the testing phase the system proves effective in automating the marking process, reducing errors, and enhancing overall efficiency for both students and educators.